Effect of COVID-19 Pandemic on Mental Health in Patients with Kidney Transplantation - Gülşah Sasak; Tahsin Karaaslan; Sabahat Alısir Ecder (Baiman Bauntung Batuah Center, 2021)
Severe acute respiratory syndrome coronavirus-2 is the cause of coronavirus disease 2019 (COVID-19). The most effective method in controlling the disease is maintaining the distance between people and, if necessary, quarantine. Recent evidence suggests that people kept in isolation and quarantine experience significant anxiety, confusion, and stress levels. This study aims to investigate the effects of COVID-19 on mental health in kidney transplant recipients. In this cross-sectional study, all renal transplant patients who followed up in our transplantation clinic were evaluated to be included in the study. The Turkish version of the fear of COVID-19 scale, depression anxiety stress scale (DASS-21), and satisfaction with life scale (SWLS) were administered to the patients. Patients were interviewed face-to-face by the same physician. A total of 68 patients were included in the study: 29 (42.6 percent) women and 39 (57.4 percent) men. In the present study, we detected that DASS-21 anxiety, depression, stress, and total scores were higher in patients with a family history of psychiatric disease than without (p<0.05). We did not find any statistical differences between patients’ demographic characteristics and fear of COVID-19 scale, DASS-21 anxiety, depression, stress, and total scores except for family history of psychiatric disease. More extensive and multi-center studies are needed to determine these patients' anxiety and depression states in the future.